Witch Trials. (16th August 2017) - Leeson, Peter T.; Russ, Jacob W.
Abstract: We argue that the great age of European witch trials reflected non‐price competition between the Catholic and Protestant churches for religious market share in confessionally contested parts of Christendom. Analyses of new data covering more than 43, 000 people tried for witchcraft across 21 European countries over a period of five‐and‐a‐half centuries and more than 400 early modern European Catholic–Protestant conflicts support our theory. More intense religious‐market contestation led to more intense witch‐trial activity. And compared to religious‐market contestation, the factors that existing hypotheses claim were important for witch‐trial activity – weather, income and state capacity – were not.